Introducing social capital into the ‘polarized pluralist’ model: the different contexts of press politicization in Portugal and Spain - Álvares, C.; Damásio, M. J. (International Journal of Iberian Studies, 2013)
This article presents the concept of social capital as complementary to Hallin and Mancini's 'polarized pluralist' model, which has been used in relation to both Spain and Portugal. In our view, while the current Spanish context may be characterized by 'partisan' journalism, this is less true of Portugal. We propose that Hallin and Mancini's polarized pluralist model be complemented by the concept of social capital to comprehend the specific underpinnings of the power constellations surrounding the press in Portugal and Spain. We will start by comparing the current situation of the press in both countries, with analysis centred on the continuities and discontinuities between past and present in a context of transition to democracy. The evolution of the press under the right-wing dictatorships of Franco and Salazar will then be historically contextualized, with the aim of drawing attention to ideological differences that may currently account for the greater political fissures between the right and left wings in Spain compared to Portugal. Lastly, we will examine the threat that the Portuguese Colonial War and the Spanish separatist movements posed to national, hegemonically defined, 'imagined communities' (Anderson 1983) and their subsequent influence on the evolution of press freedom in both countries